2016
DOI: 10.3171/2016.2.focusvid.1693
|View full text |Cite
|
Sign up to set email alerts
|

S-1 and S-2-alar-iliac screw fixation via intraoperative navigation

Abstract: Adult deformity patients often require fixation to the sacrum and pelvis for construct stability and improved fusion rates. Although certain sacropelvic fixation techniques can be challenging, the availability of intraoperative navigation has made many of these techniques more feasible. In this video case presentation, the authors demonstrate the techniques of S-1 bicortical screw and S-2-alar-iliac screw fixation under intraoperative navigation in a 67-year-old female. This instrumentation placement w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2017
2017
2018
2018

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
2
0
1
Order By: Relevance
“…In 2013, Dr. Mattei et al reported a technique involving the use of combined S-1 and S-2 SAI screws as a salvage procedure for definitive pelvic fixation after pseudarthrosis in the lumbosacropelvic junction [6]. Though the S1AI screw technique had already been used clinically [21], no anatomic parameters have been analyzed for proper trajectory of S1AI screw.…”
Section: Discussionmentioning
confidence: 99%
“…In 2013, Dr. Mattei et al reported a technique involving the use of combined S-1 and S-2 SAI screws as a salvage procedure for definitive pelvic fixation after pseudarthrosis in the lumbosacropelvic junction [6]. Though the S1AI screw technique had already been used clinically [21], no anatomic parameters have been analyzed for proper trajectory of S1AI screw.…”
Section: Discussionmentioning
confidence: 99%
“…Isolated S1-pedicle screw fixation is reported to have a high rate of pullout failure or breakage (up to 44%), and pseudarthrosis (up to 33%) (1)(2)(3). Some modified techniques have been introduced to improve the fixation strength and decrease the failure rate, including traditional iliac fixation, S1 cemented augmentation, S1 bicortical screws and S2 alar screw fixation (4)(5)(6). Traditional iliac screw fixation has improved resistance to pullout (7).…”
Section: Introductionmentioning
confidence: 99%
“…Takto lze minimalizovat rtg záření a jeho negativní vliv na operatéra i pacienta. Někteří autoři popisují své zkušenosti s roboticky asistovaným zavedením S2AI (2, 8) nebo s dopomocí navigace (12,18). Obě techniky mohou zvětšovat přesnost zavedení S2AI.…”
Section: Diskuseunclassified